Beyond NF-κB activation: nuclear functions of IκB kinase α - Huang, Wei-Chien (BioMed Central, 2013)
IκB kinase (IKK) complex, the master kinase for NF-κB activation, contains two kinase subunits, IKKα and IKKβ. In addition to mediating NF-κB signaling by phosphorylating IκB proteins during inflammatory and immune responses, the activation of the IKK complex also responds to various stimuli to regulate diverse functions independently of NF-κB. Although these two kinases share structural and biochemical similarities, different sub-cellular localization and phosphorylation targets between IKKα and IKKβ account for their distinct physiological and pathological roles. While IKKβ is predominantly cytoplasmic, IKKα has been found to shuttle between the cytoplasm and the nucleus. The nuclear-specific roles of IKKα have brought increasing complexity to its biological function. This review highlights major advances in the studies of the nuclear functions of IKKα and the mechanisms of IKKα nuclear translocation. Understanding the nuclear activity is essential for targeting IKKα for therapeutics.